Dynamic response of free span pipelines via linear and nonlinear stability analyses. (1st September 2018) - Reis, E.V.M. dos; Sphaier, L.A.; Nunes, L.C.S.; Alves, L.S. de B.
Abstract: A thorough stability analysis of submerged pipeline dynamics has been performed. The problem of current-induced vibrations in a free spanning pipeline was analyzed using both linear and non-linear methodologies. While most investigations dedicated to the analysis of this type of problem use either approximate analytical methods or traditional numerical methods, two alternative approaches are presented: Linear Stability Analysis (LSA) and the Generalized Integral Transform Technique (GITT). Although strictly valid when the pipeline is subject to small amplitude disturbances, LSA is simple to apply and yields accurate either explicit or transcendental analytical relations that predict dominant pipeline vibration frequencies and wavelengths as well as the onset of buckling. On the other hand, the GITT can predict pipeline behavior for arbitrary disturbance amplitudes more efficiently than traditional numerical methods. These features are illustrated by considering the problem of a submerged pipeline subjected to soil conditions and ocean currents. This problem was solved using LSA, the GITT and the Finite Element Method (FEM) for comparison purposes. Moreover, the DNV-RP-F105 standard was also used for verifying the proposed methods. The alternative methods offered in this paper can overcome limitations associated with traditional analytical and numerical approaches, and are employed to produce previously unreported results. Highlights: Stability analysis yields explicit and implicit correlations for pipeline dynamics. Integral transforms accurately solve linear and nonlinear pipeline dynamics. Seabed currents decrease frequencies and damp amplitudes of pipeline oscillations. Soil interaction in boundary conditions do not affect buckling conditions. Soil interaction in boundary conditions selects second instead of first unstable mode.